Carcass quality of buffalo (Bubalus bubalis) finished in silvopastoral system in the Eastern Amazon, Brazil - PEIXOTO, Maria Regina Sarkis (2013)
The influence of the diet on the quality of buffalo (Bubalus bubalis) carcasses of crossbred Murrah and Mediterranean, concentrate fed on traditional (corn/soybean) or on agro-industrial residues (palm oil and coconut cakes) was studied. The animals were sacrificed in a slaughterhouse, and physical and physical-chemical analyses in the carcasses were carried out after 24 hours, and instrumental color and texture analyses of the Longissimus dorsi were carried out 48 hours after cooling. The animals supplemented with palm oil cake had better carcass conformation and fat trim, and differences (P<0.05) in the percentage of fat in the carcass fat thickness and coverage were observed.